Comparative Assessment of Dimensionality Reduction Techniques for Multivariate Analysis of Coral Bleaching Thermal Stress - Casado, Luana D. P. E.; Lira, Ingrid G. C.; Gomes, João V. da C.; Lopes, Maximiliano A. da S.; Castro, Angélica F. de (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2026)
This paper presents a comparative analysis of seven dimensionality reduction (DR) techniques applied to the BCO-DMO global coral bleaching dataset, investigating multivariate patterns of oceanic thermal stress from 1998 to 2019. Linear Discriminant Analysis proved most effective for supervised discriminant visualization of ocean basin structure, outperforming unsupervised techniques in revealing class-defined thermal patterns within this dataset. Temporal projections reveal progressive homogenization of thermal stress across major open ocean basins and an anomalous regime shift in the Arabian Gulf, with a 30% increase in maximum thermal stress between 1998–2004 and 2012–2019. These findings highlight the potential of supervised DR as a diagnostic tool for analyzing complex environmental data through an open-source web platform that supports interactive and reproducible exploration.